2010
DOI: 10.1111/j.1600-0846.2009.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of methods used for quantifying excess water in over-hydrated skin using evaporimetry

Abstract: Little work has been carried out to establish the optimum methods and techniques needed to minimise variation in measurements of WVFD using evaporimetery. There is a need to develop more robust, standardised methods and to demonstrate their reliability for further work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Although TEWL figures varied from 0.74 to 4.32 gm 22 h 21 , all the recorded values were small compared with the 80 gm 22 h 21 or so associated with fully overhydrated skin. 34 Finally, substantial lateral contraction in fabric strips -or rucking in the skin beneath them -did not notably affect the form of tensometer curves, either.…”
Section: Resultsmentioning
confidence: 87%
“…Although TEWL figures varied from 0.74 to 4.32 gm 22 h 21 , all the recorded values were small compared with the 80 gm 22 h 21 or so associated with fully overhydrated skin. 34 Finally, substantial lateral contraction in fabric strips -or rucking in the skin beneath them -did not notably affect the form of tensometer curves, either.…”
Section: Resultsmentioning
confidence: 87%
“…For example, in recent years some progress has been made on understanding the formation of biofilms on different catheter materials under different conditions such as the pH and microbial content of the urine, 5,6 and the interactions between pad materials and skin. 7,8 However, there is still some way to go: current catheters commonly block and pads frequently cause skin damage.…”
Section: Basic Sciencementioning
confidence: 99%
“…Patch wear times between 20 and 120 min have been reported for WVFD measurements in laboratory studies on over-hydrated skin (Fader et al 2010). To investigate this issue WVFD traces from the same skin site on the same volunteers using the same fully saturated patches were measured for patch wear times between 5 and 60 min.…”
Section: Patch Wear Timementioning
confidence: 99%
“…However, evaporimetry devices are widely available and provide quantitative data which are, in principle, straight-forward to interpret. Nevertheless, a recent review of the literature (Fader et al 2010) has shown that a wide range of evaporimetry methodologies have been used, making it difficult to compare data from different studies. In addition, little work has been done to establish the repeatability of any methodology and so it is difficult to interpret data with confidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation